(untitled) (Bangladesh Journal of Scientific Research, 2014)
In this study, we compare Maximum Conditional Likelihood or MCL and Modified Score Function or MDS approach for modeling Antenatal Care (ANC) seeking behavior in matched case-control data obtained from Bangladesh Demographic and Health Survey 2007. The estimates of parameters are almost identical under both approaches. Due to the computational complexity of the MDS approach, one may prefer using the alternative computationally simpler MCL approach for the analysis of similar datasets. DOI: http://dx.doi.org/10.3329/bjsr.v26i1-2.20233 Bangladesh J. Sci. Res. 26(1-2): 75-82, December-2013